Narrow-band red-emitting phosphor with negligible concentration quenching for hybrid white LEDs and plant growth applications. Issue 14 (26th March 2021) - Singh, Kasturi; Rajendran, Marikumar; Devi, Rachna; Vaidyanathan, Sivakumar
Abstract : Narrow-band red-emitters are the key to solving problems encountered by the current white LED technology. Abstract : Narrow-band red-emitters are the key to solving problems encountered by the current white LED technology. In this context, a series of new red-emitting Li3 BaSrLa3 (MoO4 )8 :Eu 3+ phosphors were synthesized and characterized through various spectroscopic methods. All phosphor compositions were crystallized in the monoclinic phase, with space group C 2/ c . A broad charge transfer (O 2− → Mo 6+ ) extended up to the blue region along with strong 7 F0 → 5 L6, 5 D3 absorption, making them looked-for materials for warm white LED applications. The concentration quenching study reveals that there was no concentration-quenching occuring and the quantum yield of this non-concentration-quenching Li3 BaSrLa0.3 Eu2.7 (MoO4 )8 phosphor reaches 92.6%. The Li3 BaSrLa0.3 Eu2.7 (MoO4 )8 retain >80% of its emission intensity at 150 °C. The best red-emitting composition was integrated with near UV LED and obtained bright red emission with CIE x = 0.6647, y = 0.3357. White LED was fabricated by integrating the blue LED with yellow dye + red phosphor and white LED showed bright white light with CCT (5546 K), CIE (0.331, 0.385), and CRI (81%). In addition, the red LED spectrum is well-matched with the phytochrome (Pr) absorption spectrum and is useful for plant growth applications.